Study on Flood Simulation and Its Real-time Correction of Qinhuai River Basin Based on Grid-Xin'anjiang Model - SUN Wenyu; WANG Rong; YAO Cheng; HE Jian; LI Zhijia; GONG Junfu; HUANG Pengnian (Renmin Zhujiang)
There are many small and medium-sized rivers in China,with frequent floods and serious disasters,which are the key weak links in flood prevention and control.Qinhuai River system is one of the most important water bodies in Nanjing,and the possible flood disaster in the flood season poses a threat to the life and property safety in the whole city.Taking Qianhan Village in Qinhuai River basin as the research object,this paper conducts the flood simulation through the Xin'anjiang model and Grid-Xin'anjiang model,and corrects it in real time by the KNN method and feedback method,so as to realize fast and accurate flood forecasting calculation.The results show that without real-time correction,the simulation accuracy of the Grid-Xin'anjiang model is slightly better than that of the Xin'anjiang model,and the simulation results of the two models are generally good.After real-time correction,the simulation results of the Xin'anjiang model and the Grid-Xin'anjiang model are improved obviously,which can provide an important basis for the decision of flood control and disaster reduction in the Qinhuai River Basin.